EMPLOYEE PERFORMANCE BASED ON COMPETENCY, CAREER DEVELOPMENT, AND ORGANIZATIONAL CULTURE - Marnisah, Luis; Kore, Jefirstson Richset Riwu; Ora, Fellyanus Haba (Universitas Brawijaya, Indonesia, 2022)
The research objective is to analyze and prove the influence of competence, career development, and organizational culture on employee performance. For 3 (three) months, the research was carried out, starting from January-March 2022, at the Regional Secretariat of the Kupang City Government. This research belongs to quantitative research. The population in this study was 1034 employees. The number of research samples was 288, determined by proportional stratified random sampling and the Slovin technique. The Likert scale is used to obtain data from questionnaires and use observation, interviews, and documentation techniques. Data analysis used multiple linear regression analysis techniques. The results showed a positive and significant influence between career development variables and organizational culture on employee performance. In contrast, the competence variable had a negative influence on employee performance at the Kupang City Government Regional Secretariat. Competence of employees who show a negative influence shows information that the competence of employees needs to be a concern of the organization to be improved so that employees can develop from the aspect of working ability in achieving organizational goals. This study also proves that competence, career development, and organizational culture can simultaneously be used as organizational strategies to improve employee performance.